An Analytical Study Of The Effect Of Some Economic And Demographic Variables On The Unemployment Rate In Syria During The Period 2011-2018 (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study aims to know the effect of some economic and demographic variables on the unemployment rate during the period 2011-2018, including (population growth rate, economic growth rate, investment growth rate).The descriptive analytical approach was followed to give a clear picture of unemployment through analyzing the data issued by the Central Bureau of Statistics, and the statistical analysis method was used to find out the effect of economic and demographic variables on the unemployment rate, and know the relationship between these variables and the unemployment rate.The problem of the study was to answer the following question: What is the effect of economic and demographic changes on the unemployment rate during the period 2011-2018? From this main question emerges a set of sub-questions:- What is the relationship between unemployment rates and economic and demographic variables?- What is the proposed vision that can contribute to reducing unemployment rates in Syria?Among the most important results of the study:There is no statistically significant relationship between the population growth rate and the unemployment rate during the 2011-2018 study period.There is no statistically significant relationship between the economic growth rate and the unemployment rate during the 2011-2018 study period.There is no statistically significant relationship between the rate of investment growth and the unemployment rate during the 2011-2018 study period.- All the results that we reached in the body of the research were not representative of the fact of the nature of the relationship between the variables of the study, due to the fluctuation of the studied rates as a result of the turmoil and extraordinary exceptional circumstances experienced by Syria during the period of the crisis.